UPAYA PENINGKATAN KEMAMPUAN APARAT KECAMATAN DALAM PELAKSANAAN TUGAS ADMINISTRASI PEMERINTAH KECAMATAN MURUNG KABUPATEN MURUNG RAYA - Mila, Mila Rosa; Dra. Puput Ratnasari, M. Hum; Sri Mujiarti Ulfah, S.Sos. M.AP (Jurnal Administrasi Publik (JAP), 2020)
The problem in Murung Subdistrict is seen from the facilities and infrastructure, which will cause service to the community to be hampered and not maximal, so that the service in the sub-district is still complained by the community. For this reason, the purpose of service can truly be achieved as expected by the village community, so what must be considered is the presence of government officials who have adequate quality. The problem formula in this study is: "efforts to increase the ability of the sub-district apparatus in carrying out the tasks of murung sub-district administration in murung raya" The purpose of this study was to determine the ability of sub-district officials to serve their communities, and primary data obtained from interviewees by conducting interviews and direct observation. The resource persons meant were: (1). Head of sub-district head (2). Secretary of camat (3). District officials 3 people (4). Some people. This study uses a qualitative approach with a descriptive type or method. The technique of data collection is done by interviewing, documenting, and observing, in addition to the data analysis techniques in the form of data collection, data reduction, data presentation, and conclusion drawing. Based on the results of the study, it was found that the performance of employees in the sub-district in serving the community in the office of the subdistrict of Muruk, the district of Murung Raya, had not yet run optimally. So that the quality of services still needs to be improved more carefully so this will further improve their performance in serving the community, so that they can complete their tasks on time.